Desain Dan Uji Coba Media Pembelajaran Video Animasi Stop Motion Berbasis Saintifik Pada Materi Ikatan Kimia - Atika Dwi Rahmi; Zona Octarya (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This research was instigated by the students who were not able to process the knowledge gained and the lack of learning media in the learning process. This research aimed at knowing the validity and practicality levels of Scientific based Stop Motion animation video learning media on Chemical Bond lesson, especially on Ionic and Covalent Bonding. There were 5 development procedure stages using Borg and Gall model— collecting information, planning, developing the product, field testing, and revising the initial form of the product. This research was administered at State Vocational High School 2 Pekanbaru. Interview, questionnaire, and documentation were used to collect the data. Scentific based Stop Motion animation video learning media developed was tested valid by the experts of media and material with 87.14% mean percentage (very valid), and it was tested practical by 4 Chemistry subject teachers and 12 students with 92.86% mean percentage (very practical). Based on these findings, it could be concluded that Scientific based Stop Motion animation video learning media on Chemical Bond lesson was valid and practical, so it could be done the product testing at a further stage.